OPEC Market Power; Testing the Existence of Cooperative Behavior of OPEC’s Members with ARDL Approach - Seyed Mohammad Shahab Tabatabaee Atabak; Teymour Mohammadi; Morteza Khorsandi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2017)
Market power refers to the ability to affecting to the market. The firm has a pricing power in the monopoly market. One of the types of monopolies is the cartel. Two important features of behavior in form of the cartel are the impact on the amount of production and price. In terms of production, the cartel controls the production through coordination among the members, and in terms of impact on prices, it affects the price of the market by controlling production. In this study, to investigate the market power of OPEC, this issue will be discussed that whether OPEC acts as a cartel, or not? Therefore, to measure the market power of OPEC, The behavior and coordination of OPEC members’ production decisions are being studied. The research hypotheses are as follows, there is coordination in behavior and production decisions between the production of OPEC and the production of OPEC members, and total production of OPEC determines oil prices in the global oil markets. To prove the first hypothesis, used ARDL bounds testing approach of co-integration, and for the second hypothesis, used Toda-Yamamoto tests. The data used in this study includes the production of OPEC members, global oil prices (Brent, Dubai and WTI), in the period of 1994-2016, quarterly and monthly and 1980-2016, annual. The results indicates that there is no long-term relationship between the production of OPEC members and total production of OPEC, also causality from oil prices to OPEC production, also the direction of causality is from oil prices to OPEC production.